Ultrasound findings in patients with knee osteoarthritis: Relationships with clinical characteristics, radiographic findings and generalized osteoarthritis - Ahmet Sumen; Kubra Neslihan Kurt Oktay (Osteoarthritis and Cartilage Open)
Objective: To evaluate the relationship between ultrasound (US) findings and radiographic Kellgren–Lawrence (K/L) grades, symptom severity, and the presence of generalized osteoarthritis (GOA) in patients with knee osteoarthritis (OA), and to identify key US parameters associated with OA severity. Methods: This cross-sectional study included 166 patients (332 knees) with radiographically confirmed knee OA. US assessments included medial and lateral meniscus extrusion (MME, LME), suprapatellar effusion, synovitis, femoral cartilage thickness (FCT), femoral cartilage lesions, Baker's cyst, pes anserine bursitis, patellar tendinopathy, and Hoffa's fat pad pathology. K/L grades were determined by radiography. Pain and function were evaluated using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). GOA was defined as OA in five or more joints or the presence of Heberden's nodes with additional joint involvement. Results: MME showed a strong correlation with K/L grade (r ​= ​0.954, p ​< ​0.001), with 91.57 ​% exact agreement. LME showed a moderate correlation (r ​= ​0.693, p ​< ​0.001). GOA was identified in 12.65 ​% of patients and was independently associated with lower BMI, reduced FCT (<2 ​mm), and the presence of femoral cartilage lesions. Moderate correlations were observed between K/L grade and pain, WOMAC scores, and symptom duration. Conclusion: MME and FCT measured by US are strong indicators of OA severity and may help identify patients at risk for GOA. US appears to be a practical, radiation-free tool for assessing and monitoring OA progression. Further validation in larger cohorts is recommended.